Burnout in seafarers: its antecedents and effects on incidents at sea. Issue 7 (3rd October 2017) - Chung, Yi-Shih; Lee, Paul Tae-Woo; Lee, Jeong-Kwan
ABSTRACT: Seafarer health and well-being has long been a concern in the shipping industry because of the unique characteristics of working at sea. This paper aims to identify the role of burnout in seafarer health and well-being and its effect on safety. In particular, we differentiated seafarer burnout into personal and work-related burnout to reflect the ambiguous distinction between rest and work in seafarers' job environment. We also investigate the effectiveness of emotion regulation for seafarers to reduce burnout. This study proposes a conceptual framework to identify the causal relationship between occupational stress, sleepiness, emotion regulation, burnout, and incidents at sea. To verify the proposed framework, scales were adapted from established scales in the literature; a cross-sectional survey was also conducted to collect empirical data for analysis with path and simultaneous equation models. The analysis results revealed that personal and work-related burnout in seafarers are mutually affected; however, only work-related burnout exerts a direct effect on incidents. Reappraisal is an effective emotion regulation strategy in seafarers to reduce personal burnout, but not work-related burnout. Occupational stress and sleepiness exert positive effects on both personal and work-related burnout; yet, their effect on incidents is mediated by work-related burnout.